Aplicação de ozônio e ozônio + peróxido de hidrogênio para remoção de compostos recalcitrantes em lixiviados de aterros sanitários - Schoenell, Elisa Kerber (Universidade do Vale do Rio dos Sinos, 2013)
Leachates are wastewaters generated at sites of solid waste disposal through organic matter decomposition, added to infiltration waters and suspended materials. It contains biodegradable and recalcitrant compounds - difficult to biological degradation (biodegradation). This wastewater requires treatment before being disposed in the environment. The aim of this study was to evaluate the use of ozone (O3) and hydrogen peroxide (H2O2) as advanced oxidation process (AOP), in order to removal recalcitrant compounds in landfill leachate. It was used two leachates from São Leopoldo/RS landfill: raw and treated in pounds, which were treated only with O3 at a concentration of 29 mg/L (generated from the corona process) or with addition of 1000 mg/L H2O2 to O3. The tests occurred on a pilot scale, treating 460 L of leachate in each test, which lasted 96 hours. OAP (operating with the oxidants O3 and O3 + H2O2) was more efficient in the treatment of leachate that had the lowest initial concentrations of BOD, COD and TOC (both raw and treated leachate).. High removals of apparent color, COD and TOC were observed, reaching 99%, 88% and 66%, respectively. The greater removal of inorganic carbon was 23%, but the group that started with the highest concentration of these parameter, achieve the greatest removals for all others parameters studied. The addition of H2O2 increased the efficiency of removal of all parameters, but not significantly. It was observed need of additional treatment to the POA of this study.
Application of ozone and ozone + hydrogen peroxide to remove of recalcitrant compounds in landfill leachates
Keywords: Lixiviado; Compostos recalcitrantes; Processo oxidativo avançado; Ozônio; Peróxido de hidrogênio; Leachate; Recalcitrant compounds; Advanced oxidative process; Ozone; Hydrogen peroxide; ACCNPQ::Engenharias::Engenharia Civil